Comparative evaluation of the effect of curcumin and chlorhexidine on human fibroblast viability and migration: An in vitro study - Sangeetha Kolathuparambil Sukumaran; Rosamma Joseph Vadakkekuttical; Harikumar Kanakath (Wolters Kluwer Medknow Publications, 2020)
Background and Objective: Chemical plaque control acts as an adjunct to mechanical periodontal therapy. Chlorhexidine (CHX) is considered as the gold standard in chemical plaque control, but the main concern is about its fibroblast cytotoxicity. Curcumin, a lipophilic polyphenol, may offer as a promising antiplaque agent. This study was conducted to compare the effect of curcumin (0.003%, 0.03%, 0.06%, 0.1%, and 0.12%) and CHX (0.03%, 0.06%, 0.1%, 0.12%, and 0.2%) on gingival fibroblast cell viability and wound healing at different time periods (1, 2, 4, 6, 8, and 10 min). Materials and Methods: The minimum inhibitory concentration (MIC50) was determined before the evaluation of cytotoxicity and wound healing property. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and morphological examination by direct invert microscopy were carried out to determine cytotoxicity. Wound healing was evaluated by scratch wound assay. Results and Discussion: The MIC50 of CHX and curcumin was at 0.1% and 0.003%, respectively. The mean percentage of fibroblast viability at different concentrations of CHX and curcumin at each time period showed a significant difference. Curcumin exhibited less cytotoxicity as compared to CHX at all concentrations and at varying time periods. There was a significant difference between mean percentage of fibroblast viability at MIC50 of CHX (0.1%) and curcumin (0.003%) at different time periods. The difference between percentage wound healing at antibacterial concentrations of CHX and curcumin at varying time periods was significant. Conclusion: The antibacterial concentration of curcumin (0.003%) exhibits less fibroblast cytotoxicity and excellent wound healing property as compared to CHX. Curcumin may offer as a promising chemical plaque control agent which is less cytotoxic, cost-effective, safe, easily available, and with a possibly beneficial effect on wound healing.